2015
DOI: 10.12691/jfnr-3-1-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Techniques on the Quality and Acceptability of <i>A</i><i>uricularia auricula</i><i> </i>Mushroom Pickle

Abstract: The present study aimed at the formulation of pickled product, incorporated with and without mustard oil; vinegar and salt were used as preservative. The products have been evaluated for sensory attribute i.e color, flavor, texture, taste and overall acceptability, (MOVS) formulated pickle found to be excellent and have higher score 5.7, 6.5, and 7.0 for color, flavor, and overall acceptability. It was found that the polysaccharide content and pH were decreased during processing, and significant difference (P>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Only in the case of the research reported by Khaskheli et al. (), the bacterial count after 3 to 4 weeks of fermentation of Auricularia auricula fruiting bodies at a temperature of 26 ± 4 °C was slightly above 3 log cfu/g, depending on the experimental combination. However, as mentioned previously, these studies did not reflect a typical lactic fermentation process, as the recipe contained acetic acid.…”
Section: Conditions Of Lactic Fermentation and Durability Of The Finimentioning
confidence: 86%
See 4 more Smart Citations
“…Only in the case of the research reported by Khaskheli et al. (), the bacterial count after 3 to 4 weeks of fermentation of Auricularia auricula fruiting bodies at a temperature of 26 ± 4 °C was slightly above 3 log cfu/g, depending on the experimental combination. However, as mentioned previously, these studies did not reflect a typical lactic fermentation process, as the recipe contained acetic acid.…”
Section: Conditions Of Lactic Fermentation and Durability Of The Finimentioning
confidence: 86%
“…and Lactarius spp. (Zhuk‐Yu, Papilinia, & Bakaitis, ), Auricularia auricula (Khaskheli et al., ), and Cantharellus cibarius (Jabłońska‐Ryś et al., ). Termitomyces robustus was fermented as well; it is a specific mushroom with edible and, as commonly agreed, very tasty fruiting bodies grown by termites in their nests (Bello & Akinyele, ).…”
Section: Lactic Fermentation Of Mushroomsmentioning
confidence: 99%
See 3 more Smart Citations